The Influence of Brand Ambassador, Brand Image, Brand Trust on Repurchase Intention Among Consumers of AESPA Edition of Nabati Products in Surabaya - Innatus Solehah; Siti Ning Farida (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of Brand Ambassador, Brand Image, and Brand Trust on repurchase intention among consumers of Nabati Aespa edition in Surabaya. This study used a quantitative method with a descriptive and causal approach. Data were collected through a questionnaire administered to members of Mys Surabaya. Data were measured using a Likert scale, and the analysis process included validity, reliability, classical assumptions, F-test, and t-test. The results showed that simultaneously, brand ambassador, brand image, and brand trust had a significant influence on repurchase intention. Meanwhile, partially, brand ambassadors and brand image have a significant effect on repurchases, but brand trust does not. This finding indicates that brand ambassadors and brand image are more effective in encouraging repurchases than brand trust in this case. Companies can increase repurchases by strengthening the role of credible and inspiring brand ambassadors, building a positive brand image through consistent communication and engaging storytelling, and increasing brand trust through maintained product quality and satisfactory after sales service.